2014
DOI: 10.1039/c4ra12805b
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis and display of diverse metal nanoparticles by recombinant Escherichia coli

Abstract: This study used the biomolecule, eumelanin, as an agent for the reduction of metal ions. Our results demonstrate the effectiveness of synthesizing diverse metal nanoparticles through the use of recombinant E. coli expressing Rhizobium 10 65 Fig. 1 EuMel from R. etli mediates the synthesis of gold nanoparticles. (A) Photograph of solutions in the presence or absence of 1 mM L-DOPA and Au 3+ , respectively. (B) TEM image of gold nanoparticles synthesized by EuMel. Scale bar: 20 nm. (C) TEM images of R. etli cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In this way, the production of metal nanoparticles by fungi is one of the most successful strategies [ 42 , 50 , 51 , 52 , 53 ].…”
Section: Biosynthesis Of Metal Nanoparticles By Microorganismsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this way, the production of metal nanoparticles by fungi is one of the most successful strategies [ 42 , 50 , 51 , 52 , 53 ].…”
Section: Biosynthesis Of Metal Nanoparticles By Microorganismsmentioning
confidence: 99%
“…The TEM analysis demonstrated that the AuNPs showed a particle size average of around 12 nm ( Figure 10 D). The strategy was successfully applied to other metals obtaining NPs with a particle size between 7 and 13 nm [ 53 ].…”
Section: Biosynthesis Of Metal Nanoparticles By Microorganismsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the previous reports, GNCs were synthesized in vitro by using cellular extracts including reductases . Alternatively, GNCs were formed randomly inside the cells by intracellular reductive proteins such as metallothionein and phytochelation synthase expressed in recombinant microbial cells. , Similarly, GNCs were synthesized on the cell surface by reductive enzymes in extracellular polymeric substances, which play a role in microbial activity to protect cells from environmental stresses such as high salinity and extreme pH conditions, surrounding microbial cells …”
mentioning
confidence: 99%